Implementation of Envelopes as a Regulatory Degree of Freedom for Batteries Participating in Fast Frequency Response. (November 2018) - Hollinger, Raphael; Cortés, Agustín Motte; Wittwer, Christof; Engel, Bernd
Abstract: Fast frequency response services become more relevant in power systems with a high share of fluctuating renewable energy sources and decreasing shares of conventional generators. In Germany there are special requirements for providers of Primary Control Reserve (PCR) with limited storage capacity. Furthermore, regulatory degrees of freedom are available for these to control their state of charge (SoC) within allowed limits. In Great Britain, the Enhanced Frequency Response (EFR) service was developed considering storage limitations and thus introduces the concept of envelopes to support SoC maintenance. In this paper, the concept of EFR envelopes is adapted to the provision of PCR in Germany. It is shown that the dynamic use of envelopes effectively maintains SoC away from extreme values and close to 50 % for most part of the year, reducing cycling and significantly decreasing the need for corrective measures from external sources to maintain the battery's SoC.